Effects of microwave thawing on viability of rat embryonic cerebral cells cryopreserved by vitrification - HU Jun-xiang; YING Hua-bo; ZHOU Guo-ying; ZHAO Yu-qin (浙江大学学报. 农业与生命科学版)
The embryonic cerebral cells (ECC) of pregnant SD rats (17-19 days) were cryopreserved by vitrification. After cryopreservation for 3,10,20,30 and 60 days, the individual ECC samples were separately thawed in 38℃ water bath or by microwave treatment in 300 mL 10℃ water under microwave power of 800W, frequency of 2450MHz and thawing duration of 80s, following which the viability of ECC was assayed. The experimental results showed that during cryopreservation of 3-30 days, the recovery rate and the survival rate of the cells, and the activity of succinate dehydrogenase (SDH) and superoxide dismutase (SOD) of ECC were significantly depressed, whereas the hydrogen peroxide (H2O2) content of ECC was markedly increased. After cryopreservation for 30 days these indexes remained relatively stable so that no significant difference (P>0.05) was found between in these indexes before and after being preserved for 60 days. The cell survival rate, the activity of SDH and SOD of ECC subjected to microwave thawing were higher than those of ECC subjected to water bath thawing, whereas the H2O2 content of ECC of the former was lower than that of the latter. It was indicated that damage to the microwave-thawed ECC was lighter than damage to water bath-thawed ECC.